KEBIJAKAN PENDIDIKAN ANAK TERLANTAR DI PANTI ASUHAN ST. LOUIS DE MONFORT KOTA KUPANG - Maria Lusiana Roja (SocioEdu: Sociological Education, 2020)
The aims of the research are (1) to find out how the implementation of the educational policy of abandoned children at the Orphanage St. Louis De Monfort Kupang, (2) to understand how the impact of the educational policy to abandoned children at the Orphanage St. Louis De Monfort Kupang. The research used a qualitative method. The subject of the research was the Head of the St. Orphanage Louis De Monfort Kupang. The data of this research were collected through observation, interviews, notes, and documentation. The data were analyzed using qualitative analysis techniques, it consists of data collection, data reduction, data presentation, and drawing conclusions. The results of the research are the implementation of educational policies that include formal, informal and non-formal education at St. Orphanage Louis De Monfort Kupang has been implemented well in accordance with education guidelines. In the educational policy process for abandoned children, it found obstacles that are limited to education cost from the regional government. Nevertheless, educational policy has had a positive impact on the life of abandoned children. Through formal education, they can continue their education to a higher level. Formal education policy is carried out through educational institutions (schools) with good quality, which are spread in several areas at Kupang city. Informal education is carried out through three systems, they are kinship, role model and discipline to shape the character of children. While skills which are aspects of non-formal education are carried out through training, both from the orphanage itself and from collaboration with the Kupang City government.